A study on relationship between market share and cash flow policy - Somayeh Sadeghi Moghaddam; Fateme Zabihi (Management Science Letters)
This paper presents an empirical investigation to study the relationship between cash flow and market share on selected firms from Tehran Stock Exchange over the period 2007-2011. Using regression analysis, the study has detected a positive and meaningful relationship between cash flow on one side and three other investment opportunities, firm size and operating cash flow. In addition, there is a negative and meaningful relationship between leverage and cash flow. However, the study does not find any meaningful relationship between cash flow and market share. Finally, the study does not find any meaningful relationship between the cash flows of the previous year as control variable and other cashable assets.